2020
DOI: 10.3390/ijms21093296
|View full text |Cite
|
Sign up to set email alerts
|

The 15q11.2 BP1-BP2 Microdeletion (Burnside–Butler) Syndrome: In Silico Analyses of the Four Coding Genes Reveal Functional Associations with Neurodevelopmental Disorders

Abstract: The 15q11.2 BP1-BP2 microdeletion (Burnside–Butler) syndrome is emerging as the most frequent pathogenic copy number variation (CNV) in humans associated with neurodevelopmental disorders with changes in brain morphology, behavior, and cognition. In this study, we explored functions and interactions of the four protein-coding genes in this region, namely NIPA1, NIPA2, CYFIP1, and TUBGCP5, and elucidate their role, in solo and in concert, in the causation of neurodevelopmental disorders. First, we investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 47 publications
0
44
0
Order By: Relevance
“…Genetic analysis showed that these deletions were inherited from one of the normal parents. However, there are some reports of 15q11.2 deletions causing neurodevelopmental alterations 25,26 . Thus, we also defined the 15q11.2 deletions as VUS.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic analysis showed that these deletions were inherited from one of the normal parents. However, there are some reports of 15q11.2 deletions causing neurodevelopmental alterations 25,26 . Thus, we also defined the 15q11.2 deletions as VUS.…”
Section: Discussionmentioning
confidence: 99%
“…Further, mutations in this cluster have been marked as recurrent pathogenic CNV regions for neurodevelopmental disorders such as autism. Either side of its flanking regions contains autism genes such as UBE3A and ATP10A [41].…”
Section: Discussionmentioning
confidence: 99%
“…Mosaicism/tissue-specific gene expression should be considered and further studied in view of more males than females affected with ASD, particularly X-linked genes. Additionally, hormonal-mediated gender influences or differential expression in the brain should be examined for dysregulation in ASD including methylation status of brain-expressed genes on the X chromosome and interaction with autosomal genes (e.g., X-linked FMR1 gene causing fragile X syndrome [116] and CYFIP1 gene at 15q11.2 involved with coding transporter for FMR1 protein [117]). These investigations will require more specialized methods with increased sensitivity such as droplet digital PCR [118].…”
Section: Future Directionsmentioning
confidence: 99%